SARS-CoV-2 Dissemination Through Peripheral Nerves Explains Multiple Organ Injury - Fenrich, Matija; Mrdenovic, Stefan; Balog, Marta; Tomic, Svetlana; Zjalic, Milorad; Roncevic, Alen; Mandic, Dario; Debeljak, Zeljko; Heffer, Marija (Frontiers in Cellular Neuroscience, 2020)
Coronavirus infectious disease (CoVID-19), caused by recently identified coronavirus SARS-CoV-2, is characterized by inconsistent clinical presentations. While many infected individuals remain asymptomatic or show mild respiratory symptoms, others develop severe pneumonia or even respiratory distress syndrome. So far, SARS-CoV-2 is reported to be able to infect lungs, intestines, blood vessels, bile ducts, conjunctiva, macrophages, T lymphocytes, heart, liver, kidneys and the brain. More than a third of cases displayed neurological involvement, and in many severely ill patients, multiple organ injury and infection was documented. However, less than 1% of patients had a detectable level of SARS-CoV-2 in the blood, raising a question of how the virus spreads throughout the body. We propose that nerve terminals in orofacial mucosa, eyes and olfactory neuroepithelium act as entry points for the brain invasion, allowing SARS-CoV-2 to infect the brainstem. By exploiting the subcellular membrane compartments of infected cells, a feature common to all coronaviruses, SARS-CoV-2 is capable to disseminate from the brain to periphery via vesicular axonal transport and passive diffusion through axonal endoplasmic reticula, causing multiple organ injury independently of an underlying respiratory infection. The proposed model clarifies a wide range of clinically observed phenomena in CoVID-19 patients, such as neurological symptoms unassociated with lung pathology, findings of protracted presence of the virus in samples obtained from recovered patients, exaggerated immune response, multiple organ failure in severe cases with variable course and dynamics of the disease. The proposed model provides novel insights into CoVID-19 and its potential long-term sequelae, and establishes a framework for further investigations.